American English grammar : an introduction - Katz, Seth (New York : Routledge / Taylor & Francis Group, 2020)
"American English Grammar introduces students to American English in detail, from parts-of-speech, phrases, and clauses to punctuation and explaining (and debunking) numerous "rules of correctness," integrating its discussion of Standard American grammar with thorough coverage of the past sixty years' work on African American English and other ethnic and regional non-Standard varieties. The book's examples and exercises include 500 real-world sentences and longer texts, drawn from newspapers, film, song lyrics, and online media; Mark Twain, Stephen King, academic texts, translations of the Bible, poetry, drama, children's literature, and transcribed conversation and TV and radio shows. Based on 20 years of classroom testing and revision, American English Grammar will serve as a classroom text or reference grammar that teaches students how to think and talk not only about the mechanics of sentences, but about the deep and detailed soul and nuance of the most widely used language in human history"--
Includes bibliographical references and index.
HB
Description based on print version record and CIP data provided by publisher.
Keywords: English language -- United States -- Grammar; English language -- United States -- Usage; English language -- United States -- Syntax